Detection of BCR‐ABL1 mutations in chronic myeloid leukaemia by massive parallel sequencing. (17th December 2012) - Eyal, Eran; Tohami, Tali; Amir, Amnon; Cesarkas, Karen; Jacob‐Hirsch, Jasmine; Volchek, Yuliya; Nagler, Arnon; Rechavi, Gideon; Amariglio, Ninette
Summary The ability to sequence nucleic acids at an unprecedented pace and decreased costs using massive parallel sequencing (MPS) strongly affects biomedical research. Here we applied MPS for the detection of rare, clinically relevant mutations in a chronic myeloid leukaemia (CML) patient. Tyrosine kinase inhibitors revolutionized CML therapy but in some patients the disease progresses due to resistance‐conferring mutations. MPS was applied herein to monitor such mutations in BCR‐ABL1 transcripts at different time points. The large volume of sequencing data increases sensitivity compared to direct sequencing and allows detection of marginally represented and previously uncharacterized mutations. We detected changes in the frequency of mutated clones including the emergence and disappearance of the resistance‐associated ABL1 T315I mutation. We also observed correlation in appearance of adjacent mutations, and exploited this observation to demonstrate the existence of mutated clones at the time of diagnosis. A tool is provided for detection of low frequency single nucleotide variants/mutations from deep coverage MPS data, applicable to clinical translation of advanced sequencing technologies.